First total synthesis of seimatopolide B - Nookaraju, U.; Harbindu, Anand; Bhise, Ankushkumar D.; Sharma, Brijesh M.; Kumar, Pradeep (RSC Advances, 2012)
The first enantioselective total synthesis of seimatopolide B has been achieved, using ring-closing metathesis and DCC (N,N'-dicyclohexylcarbodiimide) coupling as key steps. The stereogenic centres were generated by means of iterative hydrolytic kinetic resolution (HKR) of racemic epoxides.

Concise synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate - Ramalingam, S.; Bhise, Ankushkumar D.; Show, Krishanu; Kumar, Pradeep (Arkivoc, 2013)
An efficient synthesis of (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate 1, a common intermediate for various polyhydroxylated piperidines is reported in six steps with 32% overall yield starting from Garner's aldehyde. The key steps include the diastereoselective nucleophilic addition and intramolecular cyclization. (5R,6S)-tert-butyl 5-acetoxy-6-(hydroxymethyl)-5,6-dihydropyridine-1(2H)-carboxylate is a common precursor for the synthesis of 1-deoxy-L-mannojirimycin, 1-deoxy-L-idonojirimycin, L-fagomycin and related analogues.
Keywords: cyclization; Garner's aldehyde; nucleophilic addition; polyhydroxy piperidines